Mind the gap - Kamin, Tanja (Teorija in praksa, 2017)
This paper explores the willingness to donate organs after death in relation to selected socio-demographic characteristics and organ donation-related factors. The analysis is mainly based on the Eurobarometer 72.3 survey for the Slovenian population conducted in 2009 on a probability sample of residents aged 15 years or more. The central indicator of interest is the reported willingness to donate organs after death, studied in relation to basic socio-demographic characteristics, discussion of organ donation in family, legislation awareness, and past blood donation. The study confirms the relatively high reported donation willingness among Slovenians (61.3% of Slovenians report they are willing to donate their organs after death), but with significant variations across socio-demographic characteristics. It also shows the importance of communication and knowledge for the willingness to donate. The gap between the reported willingness and those who officially register for post-mortem organ donation calls for further empirical investigation with a broader set of psychosocial factors.
Keywords: darovanje organov; Darovanje organov, tkiv ipd.; Donation of organs, tissues, etc.; Družbeni vidik; Social aspects